Population genetics of zig-zag eel (Mastacembelus armatus) uncover gene flow between an isolated island and the mainland China - Yang, Yexin; Wang, Yuanyuan; Wu, Yuli; Liu, Yi; Liu, Chao; Jiang, Zhiyong; Mu, Xidong (Frontiers in Marine Science, 2023)
Introduction Mastacembelus armatus is a commercially valuable fish, normally distributed in southern China and Southeast Asia. The natural population size of M. armatus is shrinking in recent years because of overfishing and habitat loss. In order to clarify the genetic diversity and differentiation of M. armatus populations, we collected 114 samples from eight populations in southern China and Vietnam and analyzed their population structure using nuclear ribosomal DNA sequences, the concatenated 18S and ITS2 regions. Methods Genomic DNA from the fin clip was extracted and sequenced on an Illumina novaseq 6000 (Illumina, USA) high-throughput sequencing platform in accordance with the manufacturer’s instructions. After assembly and annotation, haplotype diversity, TCS network analysis, AMOVA analysis, population pairwise genetic distances, and UPGMA tree construction were conducted based on the concatenated sequences of 18S and ITS2. Results and discussion In total, eleven nrDNA haplotypes were detected based on the concatenated sequences of 18S and ITS2. Amongst, three haplotypes were the main haplotypes, as representatives of three corresponding Clusters. There were two major Clusters in China, however, the Cluster in Vietnam was significantly divergent from the other two in China, likely due to the lack of river connection between China and Vietnam. Interestingly, based on low FST value, we found that gene flow occurred between the isolated island, Hainan Province, and the mainland China of Guangxi Province, probably as a result of exposed continental shelf connected them during glacial periods. In general, combing our data and literature data, genetic diversity and differentiation of M. armatus populations are relatively high regardless of spatial scale, although their natural population size is declining. This suggests that it is not too late to adopt measures to protect M. armatus, which benefits not only species itself but also the whole ecosystem.